2019
DOI: 10.1002/slct.201902245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Aryl‐12H‐benzothiazolo[2,3‐b]quinazolin‐12‐ones and Their Activity Against Monoamine Oxidases

Abstract: Benzothiazoloquinazolines are known to possess several interesting biological properties. Various arylated benzothiazoloquinazolines were synthesized from readily available 2‐bromo‐12H‐benzothiazolo[2,3‐b]quinazolin‐12‐one by palladium catalysed Suzuki‐Miyaura reactions in 43 – 85% yield. Synthesized derivatives were analysed regarding their in vitro inhibition activity towards monoamine oxidases A and B and showed significant inhibitory values in the micromolar range. Molecular modelling as well as PAINS stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 22 publications
(5 reference statements)
0
27
0
1
Order By: Relevance
“…Among all evaluated compounds, 4 h was found as the most potent and selective inhibitor of MAO−A with an IC 50 ± SEM value of 0.42 ± 0.01 μM, followed by 4 g and 4 e showing strong inhibition values of 1.04 ± 0.06 and 4.01 ± 0.22 μM, respectively. Compound 4 h proved to be considerably more active against MAO−A than the best derivative of our recently reported 2‐aryl‐12 H ‐benzothiazolo[2,3‐ b ]quinazolin‐12‐one series (2.82 μM) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all evaluated compounds, 4 h was found as the most potent and selective inhibitor of MAO−A with an IC 50 ± SEM value of 0.42 ± 0.01 μM, followed by 4 g and 4 e showing strong inhibition values of 1.04 ± 0.06 and 4.01 ± 0.22 μM, respectively. Compound 4 h proved to be considerably more active against MAO−A than the best derivative of our recently reported 2‐aryl‐12 H ‐benzothiazolo[2,3‐ b ]quinazolin‐12‐one series (2.82 μM) …”
Section: Resultsmentioning
confidence: 99%
“…Substitution with 3‐trifluoromethylbenzylamine 4 e is noticed as a potent inhibitor for both isoforms with slightly reduced inhibitory activity towards MAO−A. Analogously, in our previous study on corresponding 2‐aryl‐12 H ‐benzothiazolo[2,3‐ b ]quinazolin‐12‐ones, compounds substituted by fluorinated aryl moieties were identified as the most potent inhibitors among the tested derivatives . Hence, these results indicate a positive impact of aryl fluoride substituents on the inhibitory activity of 12 H ‐benzothiazolo[2,3‐ b ]quinazolin‐12‐ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Due to the important academic values and practical applications of 12H-benzo [4,5]thiazolo[2, 3-b]quinazolin-12ones in organic and pharmaceutical chemistry, a series of synthetic strategies have been developed to construct these compounds. 7 For example, Huang and co-workers developed a simple and efficient synthesis of 12H-benzo [4,5]thiazolo[2, 3b]quinazolin-12-ones by copper-catalyzed domino reaction of isatins and 2-bromobenzo[d]thiazoles (Scheme 1a). 8 Phan and co-workers demonstrated that 12H-benzo [4,5]thiazolo[2, 3b]quinazolin-12-ones could be prepared by a copper-catalyzed oxidative C−C bond cleavage pathway (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
“…喹唑啉酮类衍生 物还对乙酰胆碱酶 [21] 和丁酰胆碱酶 [22] 有抑制活性, 该 类化合物对结核分支杆菌也有抑制活性 [23] . 该类化合 物对单胺氧化酶 A [24] 及单胺氧化酶 B [25] 亦有抑制活性, 有望成为治疗神经退行性疾病帕金森病的先导药物. 由金属催化反应 [26] 、 微波辐射 [27] 和常规加热 [28] 等方 法已成功获得结构多样的喹唑啉酮骨架.…”
unclassified